2017
DOI: 10.1016/j.brs.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation improves locomotion and neuronal populations in a model of Parkinson's disease

Abstract: Background Parkinson’s disease (PD) is a progressive, neurodegenerative disorder with no disease-modifying therapies, and symptomatic treatments are often limited by debilitating side effects. In PD, locus coeruleus noradrenergic (LC-NE) neurons degenerate prior to substantia nigra dopaminergic (SN-DA) neurons. Vagus nerve stimulation (VNS) activates LC neurons, and decreases pro-inflammatory markers, allowing improvement of LC targets, making it a potential PD therapeutic. Objective To assess therapeutic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 66 publications
5
65
0
Order By: Relevance
“…Previous studies have shown that in the rodent model of PD induced by 6-OHDA, there were no anatomical changes of catecholaminergic neurons in the LC (Farrand et al, 2017;Ostock, Lindenbach, Goldenberg, Kampton, & Bishop, 2014;Shin et al, 2014;Tuppy et al, 2015), which was confirmed by the present study. Previous findings also demonstrated in a rat model of PD that central chemoreception is initially reduced, but then recovers during the course of PD (Oliveira et al, 2017).…”
Section: Neural Control Of Breathing In Animals With Induced Pdsupporting
confidence: 92%
“…Previous studies have shown that in the rodent model of PD induced by 6-OHDA, there were no anatomical changes of catecholaminergic neurons in the LC (Farrand et al, 2017;Ostock, Lindenbach, Goldenberg, Kampton, & Bishop, 2014;Shin et al, 2014;Tuppy et al, 2015), which was confirmed by the present study. Previous findings also demonstrated in a rat model of PD that central chemoreception is initially reduced, but then recovers during the course of PD (Oliveira et al, 2017).…”
Section: Neural Control Of Breathing In Animals With Induced Pdsupporting
confidence: 92%
“…In our study pVNS improved microglial morphology after LPS injection, with more cells retaining ramified branches as found under homeostatic states. As anticipated, pVNS reduced microglial activation, including Iba-1 and CD68, at 24 h in a manner similar to other VNS approaches [13, 37, 38]. These effects on glia activation may result from the systemic anti-inflammatory effects of VNS leading to a reduction in the overall neuroinflammatory burden, including Toll-like receptors signaling, rather than through a direct action as mediated through α7 nAChRs on microglia cells.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, it has been reported that VNS administered for 10 days improved locomotion in a rodent model of PD [151]. Thus, an observational, open-label, pilot study explored the effect of single-dose, noninvasive VNS on gait pattern and FOG in 12 patients with FOG.…”
Section: Noninvasive Vagus Nerve Stimulation (Vns)mentioning
confidence: 99%
“…The mechanism was still unknown. One possibility is that locus coeruleus noradrenergic neurons degenerate prior to substantia nigra dopaminergic neurons in PD, and VNS may activate locus coeruleus neurons [151]. A multicenter, doubleblind, placebo/sham-controlled randomized trial of noninvasive VNS in patients with PD are needed.…”
Section: Noninvasive Vagus Nerve Stimulation (Vns)mentioning
confidence: 99%